A Comparison of the Incidence and Type of Ocular Motility Defects in Patients Presenting to Birmingham Midland Eye Centre Emergency Department during 2019 and 2020 to Assess the Impact of the Covid-19 Pandemic. Issue 1 (20th September 2022) - Edwards, Jessica; Russo, Eilidh; Auld, Rosie
Aim: This audit aimed to investigate whether COVID-19 had any impact on the incidence and type of ocular motility defects in patients presenting to Birmingham Midland Eye Centre (BMEC) Emergency Department (ED) during the COVID-19 pandemic in 2020 compared to the previous year. Methods: Medical records were reviewed for all patients presenting to BMEC ED during 2019 and 2020. Patients were classified depending on their diagnosis. The incidence and classification of ocular motility defect were analysed. Factors considered during analysis were number of presentations by year and month; COVID-19 tests; and pre-existing conditions. Results: Two hundred and twenty-one patients presented in 2019, and 260 patients in 2020, an increase in incidence of 17.6% was observed. One hundred and eighty-five patients were classified with new-onset neurogenic conditions in 2019, and 222 patients in 2020, an increase of 20.0%. In 2020, most patients presented in July, November, and December. Overall, there was a 91.3% increase in new-onset fourth cranial nerve palsies in 2020. Fifty-seven patients in 2020 had a Polymerase Chain Reaction COVID-19 test, of these 5 were COVID-19 positive. Conclusion: There was a higher incidence of ocular motility defects in 2020 compared to 2019. The majority of ocular motility defects were classified as neurogenic. It is difficult to attribute this increase to COVID-19 due to lack of testing and results, and confounding variables such as pre-existing conditions and lockdown restrictions. Some potential explanations for the change in presentations across the year of 2020 are proposed.